Valorization of Spent coffee Grounds: A sustainable resource for Bio-based phase change materials for thermal energy storage. (15th February 2023) - Jin Ong, Pin; Leow, Yihao; Yun Debbie Soo, Xiang; Hui Chua, Ming; Ni, Xiping; Suwardi, Ady; Kiang Ivan Tan, Chee; Zheng, Rongyan; Wei, Fengxia; Xu, Jianwei; Jun Loh, Xian; Kai, Dan; et al.
Graphical abstract: Highlights: Spent coffee grounds as a sustainable resource for phase change material. Extracted coffee oil with a melting point of 4.5 °C and latent heat of 51.1 J/g. Potential use of coffee oil for low-temperature thermal energy storage applications. Abstract: Spent coffee grounds (SCGs) are waste residues arising from the process of coffee brewing and are usually sent to landfills, causing environmental concerns. SCGs contain a considerable amount of fatty acids and is therefore a promising green alternative bio-based phase change material (PCMs) compared to conventional organic and inorganic PCMs. In this study, the extraction of coffee oil from SCGs was conducted using three different organic solvents-ethanol, acetone, and hexane. The chemical composition, chemical, and thermophysical properties of these coffee oil extracts were studied to evaluate their feasibility as a bio-based PCM. Gas chromatography-mass spectroscopy (GC–MS) analysis indicated that coffee oil contains about 60–80 % of fatty acids while the phase transition temperature of the coffee oil extracts is approximately 4.5 ± 0.72 °C, with latent heat values of 51.15 ± 1.46 J/g as determined by differential scanning calorimetry (DSC). Fourier Transform Infrared Spectroscopy (FTIR) and DSC results of coffee oil extracts after thermal cycling revealed good thermal and chemical stability. An application study to evaluate coffee oil extract as a potential cold therapy modality showed that it can maintain temperatures below normal body temperature for up to 46 min. In conclusion, this work exemplifies the potential of SCGs as a promising green and sustainable resource for bio-based PCMs for low-temperature thermal energy storage applications such as cold-chain transportation and cold therapy.